2015
DOI: 10.1176/appi.ajp.2015.14070818
|View full text |Cite
|
Sign up to set email alerts
|

The Intergenerational Transmission of Anxiety: A Children-of-Twins Study

Abstract: Objective. The transmission of anxiety within families is well-recognised, but the underlying processes are poorly understood. Twin studies of adolescent anxiety demonstrate both genetic and environmental influence, and multiple aspects of parenting are associated with offspring anxiety. To date, the Children-ofTwins design has not been used to evaluate the relative contributions of genetic versus direct transmission of anxiety from parents to their offspring. Method. Anxiety and neuroticism measures were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
160
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(181 citation statements)
references
References 44 publications
13
160
1
5
Order By: Relevance
“…The finding that inherited influence had a trivial effect on the developmental trajectory of a child anxiety symptoms and a small effect on overall symptom levels at 18 months is consistent with recent children of twins work showing that an environment pathway, but not a genetic one, significantly predicted child anxiety symptoms (Eley, et al, 2015). Eley et al concluded that although the lack of evidence for a genetic pathway…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The finding that inherited influence had a trivial effect on the developmental trajectory of a child anxiety symptoms and a small effect on overall symptom levels at 18 months is consistent with recent children of twins work showing that an environment pathway, but not a genetic one, significantly predicted child anxiety symptoms (Eley, et al, 2015). Eley et al concluded that although the lack of evidence for a genetic pathway…”
Section: Discussionsupporting
confidence: 55%
“…The 'children-of-twins' design enables genetic transmission to be separated from environmental transmission and in a recent example by Eley et al (2015), data from 385 monozygotic and 486 dizygotic same-sex twin parents and their offspring (aged 11 to 22) were analyzed. The study showed that environmental mechanisms account for parentchild similarity but the data were equally consistent with children's anxiety affecting parental symptoms as the reverse.…”
Section: Parental Influence On Childhood Anxietymentioning
confidence: 99%
“…Cognitive vulnerability is suggested to interact with familial risk (e.g., negative and aversive family or peer experiences, insecure attachment with caregivers; Affrunti & WoodruffBorden, 2015; review by Waite, Whittington & Creswell, 2014), and exposure to specific threat experiences and challenging life events (e.g., Muris & Merkelbach, 2001;Oar, Farrell, & Ollendick, 2015;Rachman, 1998;Rapee, 2001). For example, while children inherit genes that increase vulnerability for anxiety (Hancock, Mitrou, Shipley, Lawrence & Zubrick, 2013;Micco et al, 2009), they are also more likely to experience an anxiogenic parenting style that can include parent over-control, parent modeling of anxiety and distress, and the sharing of negative information and avoidance of feared objects or events (Eley, 2015;review by Creswell Murray, Stacey & Cooper, 2011).…”
mentioning
confidence: 99%
“…Det er påvist en klar sammenheng mellom det å vokse opp med psykisk syke eller rusmisbrukende foreldre og skadevirkninger hos barna (1)(2)(3)(4)(5). Det er risiko for at foreldrenes psykiske eller rusrelaterte vansker påvirker deres funksjon som forelder, og dermed negativt påvirker miljøet barna oppholder seg i (1,3,6).…”
unclassified
“…Det er risiko for at foreldrenes psykiske eller rusrelaterte vansker påvirker deres funksjon som forelder, og dermed negativt påvirker miljøet barna oppholder seg i (1,3,6).…”
unclassified